The Polyphony of Closed Space in the Contemporary Saudi Narration - al- Moghairi, Mishal Fadhi (Arab Journal for Sciences and Research Publishing, 2020)
This study is based on studying the closed horizon in Saudi novels examining suggestiveness from these literary works. These reflections express either the author or the addressee’s stream of consciousness attributed to social factors like poverty, heartbreaking, sadness, and fear. The constructive approach was employed here. The structure of the study is divided into introduction with emphasis on identifying the concept of the horizon in novels generally. Then, there is a detailed discussion to various issues related to the main topic of the paper related to the closed horizon semantically with different lexemes and interactively with different characters. The study concluded that a text with multiple horizons creates excitement, and use closed horizon in novels to express intentional suggestiveness. Further, it demonstrates the level of how Saudi novelists adopt a closed horizon in their literary works.